Apgar Score and Umbilical Cord Gas as Quality Markers for Identification of Unindicated Cesareans [35N]. (May 2017) - Metz, Torri; Hermesch, Amy; Allshouse, Amanda; Alston, Meredith; Babcock Gilbert, Sara Ann; Saade, George
Abstract : INTRODUCTION: To evaluate if either a 1-minute Apgar 7 or greater, or umbilical artery (UA) pH 7.2 or greater can be used as a quality measure to identify unindicated cesarean deliveries (CD) for non-reassuring fetal heart rate (NRFHR). METHODS: Retrospective cohort of nulliparas with no contraindication to vaginal delivery. Individual physician CD rates were calculated. Two quality measures were investigated as indicative of normal neonatal status: (1) 1-minute Apgar 7 or greater, (2) UA pH 7.2 or greater. Pearson's correlation was calculated between individual physician CD rates and proportion of CDs performed with a primary indication of NRFHR but normal neonatal status. A random sample of 60 FHR tracings from women who had a CD for NRFHR were reviewed by 3 obstetricians blinded to Apgars and gases to determine if CD was indicated. RESULTS: 2, 224 women were included. Of 537 CDs, 181 (34%) had a primary indication of NRFHR. Individual physician CD rates and rates of CD for NRFHR with normal neonatal status were moderately correlated (Apgar rho=0.53, 95%CI 0.12-0.79, UA pH rho=0.53, 95%CI 0.11-0.79). CDs were identified by peer review to be unindicated in 65% of cases with a UA pH of 7.2 or greater, compared to only 28% of cases with a pH less than 7.2 (p=0.04). A high proportion of CDs with 1-minute Apgar 7 or greater were also unindicated (70% vs 57%, p=0.42). CONCLUSION: Performance of a CD for NRFHR with UA pH 7.2 or greater may help identify physicians with higher CD rates and cases that may benefit from peer review.